2006
DOI: 10.1016/j.canlet.2005.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism at codon 133 of the RASSF1 gene is preferentially associated with human lung adenocarcinoma risk

Abstract: The RASSF1 gene, a putative tumor suppressor gene located on human chromosome 3p21, garners much attention for the frequent allelic loss and gene silencing via promoter hypermethylation in a variety of human malignancies. An association between a single nucleotide polymorphism (SNP) at codon 133 of the RASSF1 gene, encoding either alanine (GCT) or serine (TCT), and human cancer risk remains undefined. We therefore, investigated the distribution of the Ala133Ser SNP in 101 patients with lung cancer, 63 with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…However, mortality is typically caused by metastasis into other substantive organs, rather than as a direct consequence of primary carcinoma (Singh et al, 2012;Stanford et al, 2014). Studies have revealed that the oncogenesis and progression of lacrimal gland carcinoma are regulated by multiple genetic functions, forming complicated mechanisms including activation of oncogenes and inactivation of tumor suppressor genes caused by gene loss, mutation, and replacement (Kanzaki et al, 2006). The tumor suppressor gene RAS association domain family gene 1 (RASSF1) was identified in human chromosome 3p21.3 in 1982 (Whang-peng et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…However, mortality is typically caused by metastasis into other substantive organs, rather than as a direct consequence of primary carcinoma (Singh et al, 2012;Stanford et al, 2014). Studies have revealed that the oncogenesis and progression of lacrimal gland carcinoma are regulated by multiple genetic functions, forming complicated mechanisms including activation of oncogenes and inactivation of tumor suppressor genes caused by gene loss, mutation, and replacement (Kanzaki et al, 2006). The tumor suppressor gene RAS association domain family gene 1 (RASSF1) was identified in human chromosome 3p21.3 in 1982 (Whang-peng et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic polymorphisms are considered to be molecular markers that predict the risk, progression and prognosis of various cancers (3)(4)(5)(6)(7). Indeed, single nucleotide polymorphisms (SNPs) in several genes are reported to be associated with the risk of lung cancer (8)(9)(10), for example SNPs in the caspase-3 and vascular endothelial growth factor genes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few molecular epidemiological studies have investigated the association between the RASSF1A Ala133Ser polymorphism and the cancer risk including breast cancer (Schagdarsurengin et al, 2005;Gao et al, 2008;Bergqvist et al, 2010;Donninger et al, 2011), lung cancer (Kanzaki et al, 2006;Xiao et al 2012), colorectal cancer (Kanzaki et al, 2006), head and neck cancer (Kanzaki et al, 2006), esophageal cancer (Kanzaki et al, 2006;Zhou et al, 2013), renal cell carcinoma (Kawai et al, 2012), hepatocellular carcinoma (Bayram, 2012), gastric cancer (Zhou et al, 2013), prostate cancer (Meyer et al, 2013). However, no consistent conclusion has been drawn.…”
Section: Research Articlementioning
confidence: 99%
“…Each group in these studies was considered separately. Thus, a total of 14 case-control studies including 4572 cases and 4320 controls were analyzed in this meta-analysis (Schagdarsurengin et al, 2005;Kanzaki et al, 2006;Gao et. al, 2008;Xiao et al 2009;Bergqvist et al, 2010;Donninger et al, 2011;Bayram, 2012;Kawai et al 2012;Meyer et al, 2013;Zhou et al, 2013).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation